The association of early childhood nutrition and growth with the intestinal microbiome and pneumonia - Budree, Shrish (Department of Paediatrics and Child Health, 2025)
Background Malnutrition and pneumonia contribute significantly to under-5 mortality. The gut microbiome is associated with development of malnutrition and pneumonia. However, data on longitudinal growth, infant feeding practices, and the microbiome in children with malnutrition and pneumonia in low and middle-income countries (LMIC) are scarce. This work aimed to investigate growth in early childhood, and associations of the microbiome with growth and pneumonia in an LMIC. Methods A prospective study of growth, pneumonia, and the microbiome was performed in the Drakenstein Child Health Study (DCHS), a birth cohort in a low-income setting in South Africa. Mothers enrolled antenatally, and mother-child pairs were followed through birth and early childhood. Comprehensive health, socio-demographic, nutritional, and psychosocial data were collected longitudinally from birth through 3 years. Anthropometry was measured by trained study staff. Dietary information was collected using food-frequency questionnaires. Active surveillance for World Health Organization (WHO)-defined pneumonia was undertaken. Longitudinal stool samples were collected at study visits and during pneumonia episodes. WHO z-scores were calculated, and malnutrition classified as stunted, wasted, or overweight/obese. Dietary data were analysed using WHO infant and young child feeding indicators. Microbiome 16S ribosomal RNA (rRNA) gene amplicon sequencing was performed and bioinformatic analysis conducted in QIIME2 and Phyloseq (R packages). Results Subsets of children in the DCHS were analysed. Growth analysis among 792 infants (50% female; 15% preterm) showed that birth weight was a significant determinant of growth (p<0.001). Stunting was highly prevalent (17% and 13% at 2 and 12 months, respectively). Feeding practices evaluated in 1076 infants (50% female, 17% preterm) showed low exclusive breastfeeding rates (13%), and high consumption of inappropriate foods (high sugar or high-fat food) at 1 year (91%). Microbiome analysis of 138 children aged 1–40 months (49% females) included 90 children with pneumonia (10% hospitalised) and 48 non-pneumonia controls. Stunted children had low diversity (p=0.009) and significant depletion in Ruminococcus (q=0.03). Compared with age-matched controls, dysbiosis was found during pneumonia episodes and before the onset of pneumonia, characterised by significant enrichment in (Escherichia coli) E. coli (q=0.04). 6 Conclusion Malnutrition and poor infant feeding practices were highly prevalent despite strong primary healthcare programs. Correction of microbiome disruption may improve outcomes in pneumonia and malnutrition.